BIG FIVE PERSONALITY TRAITS, DEMOGRAPHY AND OVERCONFIDENCE - Latifah Putranti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2020)
This study aims to determine the factors that influence overconfidence in student investors in Yogyakarta. This study explores the relationship between demographic factors (sex, age, education) and big five personality traits (agreeableness, concientiousness, extraversion, neuroticism, openness) with overconfidence. Primary data collected from student investors through questionnaires. The statistical method used is chi-square to determine the relationship between demographic factors and overconfidence. Regression method to determine the relationship between personality types with overconfidence. Analysis using SPSS for Windows 20 on 100 sample sizes. The results of the regression analysis showed that there was an influence between concientiousness, extroversion and openness personality type variables on overconfidence. Agreeableness and neuroticism have no effect on overconfidence. The study also found an influence between demographic factors (sex, age, education) and overconfidence.